THE ALTERNATIVE STRATEGIES FOR TEACHING READING SKILL FOR EFL STUDENTS - Maizarah Maizarah (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Reading is one of the important skill should be taught by EFL students, because through reading students will get many informations about anything. But, the problem is they complicated to understand the text was given by the teacher. The EFL students getting confuse to comprehend what the information of the reading text that actually wants to be delivered by the writer. It was indicated by the lack of vocabularies, less of background knowledge, and the different of English language structure with their first language or their mother tongue. In this case, the EFL students need an appropriate strategy to solve their problem. The teacher must apply some appropriate strategies to teach reading in order to make the reading activities in classroom become interesting in order to EFL students have the way to comprehend the text easily. Therefore, this article explains some alternative stratetegies that can be applied by the teachers to improve the students’ reading skill.